Poultry farmers’ adaptation to climate change in Enugu North Agricultural Zone of Enugu State, Nigeria - Jane M Chah; E Odo; A N Asadu; I N Enwelu (Journal of Agricultural Extension, 2013)
The study surveyed the perceived effect and adaptation of climate change on poultry production in Enugu-North Agricultural Zone of Enugu State. A questionnaire/interview schedule was used to collect information from 60 poultry farmers. Percentage and mean score were used to analyze the data. Reduced body weight (M=3.1); reduced fertility (M=3.3) and reduced feed intake (M=3.1) were perceived by farmers as effects of climate change on poultry. Coping strategies used by farmers included keeping of resistant varieties (56.5%); adapting extensive poultry management (65.8%) and keeping other livestock (53.8%). Respondents perceived climate change as excessive sunshine (90%); excessive rainfall (80%) and increased incidence of drought (66%). The perceived causes of climate change included burning of fossil fuels from industries (M=4.2); burning of firewood (M=4.0) and deforestation (M=3.7). Sources of information available to the farmers were radio (33.3%); farmers’ meeting (28.3%), and friends (26.7%). Technical innovations (adaptation measures) should be made available to farmers to enable them cope with the challenges of climate change.